UPAYA ORGANISASI IPNU IPPNU DALAM MENINGKATKAN KEMAMPUAN BERFIKIR KRITIS ANGGOTA DI KECAMATAN NGRONGGOT KABUPATEN NGANJUK - Nisa, Irma Khoirun (Kajian Moral dan Kewarganegaraan, 2023)
This study aims to analyze the organizational efforts of the Branch Children's Association (PAC) of the Nahdlatul Ulama Student Association (IPNU) of the Nahdlatul Ulama Student Association (IPPNU) in improving the critical thinking skills of members in Ngronggot sub-district, Nganjuk district. Critical thinking is thinking that can be digested by reason and reflective that focuses on decision-making patterns about what to believe. In the IPNU IPPNU Ngronggot PAC organization, there are several activities that are considered capable of improving critical thinking skills. These activities broadly consist of three types of activities, namely cadre activities, training activities, and discussion activities which researchers then analyze based on Ennis' (1996) theory of critical thinking elements, namely Focus, Reason, Inference, Situation, Clarity, Overview which is commonly abbreviated as FRISCO. The method used in this research is qualitative research with data collection techniques of observation, interviews, and documentation. As for the informants in this study are the Chairperson of PAC IPPNU Ngronggot, Secretary, WAKA department of Cadre, Organization, and Department of Networking Boarding Schools and Schools. To strengthen the research, the researcher conducted an interview with one of the members and alumni of PAC IPNU IPPNU Ngronggot. The conclusion of this research is that cadre activities, training activities, discussion activities are able to improve critical thinking skills by using the FRISCO critical thinking elements from Ennis (1996), although less than perfect. The results in this study are expected to be able to provide benefits and contributions in efforts to improve critical thinking skills in the organizational environment and can increase knowledge about critical thinking efforts for writers and readers in general.